2018
DOI: 10.1002/pcr2.10024
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization behavior of polypropylene/graphene nanoplatelets composites

Abstract: Interest in graphite fillers has grown since the separation of graphene from graphite by micromechanical cleavage. The object of the article is to understand the influence of graphene nanoplatelets (GNPs) with different sizes on the crystallization behavior of a polyolefin matrix such as polypropylene (PP), after elaboration by melt mixing and compression molding. Composites with volume fractions of graphene nanoplatelets ranging from 0.3 to 2 vol% were prepared. The particle dispersion states in the composite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 31 publications
2
4
0
Order By: Relevance
“…Instead, relatively large amounts of γ phase are obtained as visible from the [117] γ peak in Figure 9. Most of these findings are in agreement with the results by Beuguel et al [65], who showed epitaxial growth of crystals from graphene nanoplatelets. This is also shown in the SEM micrograph of Figure 8b, and in particular transcristallinity from the oriented agglomerates, however no γ phase was observed in that work.…”
Section: Morphologysupporting
confidence: 93%
See 1 more Smart Citation
“…Instead, relatively large amounts of γ phase are obtained as visible from the [117] γ peak in Figure 9. Most of these findings are in agreement with the results by Beuguel et al [65], who showed epitaxial growth of crystals from graphene nanoplatelets. This is also shown in the SEM micrograph of Figure 8b, and in particular transcristallinity from the oriented agglomerates, however no γ phase was observed in that work.…”
Section: Morphologysupporting
confidence: 93%
“…130 °C, as typical of the best nucleating agents commercially available [63]. This behavior has been reported in the past for a number of fillers including clay, nanotubes and graphitic platelets [35,55,64], and most recently by Beuguel et al [65]. The crystallization temperature, taken as a proxy for nucleation efficiency, increases with increasing filler loading.…”
Section: Morphologysupporting
confidence: 64%
“…12 A similar trend of increase in the crystallization onset temperature was also reported in the literature. [24][25][26][27] In addition, a higher increase in crystallization onset temperature for nanocomposites based on Homo-PP compared to Copo-PP means that the Homo-PP structure is more prone to crystallization than Copo-PP. In addition, considering the crystallization enthalpy, ΔH c showed a higher crystallinity level of Homo-PP in comparison with Copo-PP as anticipated from their molecular structures.…”
Section: Crystallization and Melting Properties Of Gnp Based Pp Nanoc...mentioning
confidence: 99%
“…Furthermore, the GnP c -axis would merge with the PP b -axis in such a way that the (002) GnP plane is matched with the (010) α PP planes, specifically the (040) α and (060) α planes. The effect of the reinforcements to induce epitaxial growth is quantified by considering the ratio of (040) α and (110) α intensities (i.e., I (040) α / I (110) α ). ,, For instance, I (040) α / I (110) α increases to 7.92 and 3.18 for PPGnP0.5 and PPGnP0.5GF10, respectively, relative to Neat PP (1.28). However, for the GF-reinforced biphasic counterpart (i.e., PPGF10), this ratio is equal to 1.25, indicating that GF has no effect on epitaxial growth of PP.…”
Section: Resultsmentioning
confidence: 99%